Ikon, Indeks, dan Simbol dalam Cerpen Tiga Cerita tentang Lidah Karya Guntur Alam - Dewi Ratnaningsih; Rahmat Prayogi (Edukasi Lingua Sastra, 2020)
This article discusses icons, indexes, and symbols in a short story. The semiotic approach is used as a literary approach to discuss this. The short story to be analyzed is the short story Three Stories About the tongue by Guntur Alam. The titles are (1) the death of the bitter tongue, (2) the tongue which tells of jurai; (3) Storyteller Tongue Wars. Each story title will be analyzed using icon, index, and symbol theory. Following is the explanation of the analysis results of the three story titles. Study of icons, indexes, and symbols in the death of the bitter tongue. The icon in the story of the death of the bitter tongue can be seen from the word "bitter tongue", the index can be seen from the incident "the death of the character Mak Yun", and the symbol can be seen from the people's actions, namely distrust of the medical world. Study of icons, indices, and symbols in Tongues that tell the story of jurai. The word Ebok is an icon of a father figure who has passed away. The index can be seen from the condition / fact that the father of my character is a bad person (has two wives). Symbols can be seen from the word sharp nosed, dark skin, bridesmaids, curly hair with thick lips are symbols of someone who is hedonistic. Study of icons, indexes and symbols in the Storyteller's Tongue War. The word coffee shop or coffee shop is an icon of the setting where the tongue war took place. The index was marked on the incident of the tongue war between Cik lam and Cik Mim. Symbol seen from the word grunt which means to breathe hard which indicates a heartbeat that is also beating fast (anger).